Pathophysiology of Psoriasis: A Review - M. Hassan, Ruqaya; Sh. Raheem, Yousif; N. Modher, Mawj; Hussein, Sarmed Mohammed (American Journal of Biology and Natural Sciences, 2025)
A persistent immune-related reactive body disorder, psoriasis, with keratinocyte hyperproliferation and immune system dysfunction. Genetics, environment, and cytokine-mediated inflammation cause illness. The IL-23/Th17 axis is crucial, since Th17 cells release cytokines such as IL-17, IL-22, and TNF-α, causing epidermal hyperplasia, impaired barrier function, and persistent inflammation. Genetic studies have connected HLA-Cw6 to susceptibility loci such as PSORS1 on chromosome 6p21. As activated dendritic cells, T cells, and keratinocytes perpetuate inflammation, innate and adaptive immune responses prolong illness. Psoriatic arthritis, heart disease, and insulin resistance are immunopathological outcomes of the condition. Biological treatments targeting TNF-α, IL-17, and IL-23 have changed therapy, significantly reducing illness. These developments do not eliminate therapeutic difficulties such as medication response variability and return of disease after treatment. The microbiome, epigenetic alterations, and new immunological targets are being studied to provide more effective, tailored treatments. Psoriasis therapy and patient outcomes depend on understanding the molecular processes of the disease.